The digital nexus : identity, agency, and political engagement - Foshay, Raphael, 1950- (Edmonton, Alberta : AU Press, 2016)
"Over half a century ago, in The Gutenberg Galaxy (1962), Marshall M cLuhan noted that the overlap of traditional print and new electronic m edia like radio and television produced widespread upheaval in personal and public life: Even without collision, such co-existence of technolo gies and awareness brings trauma and tension to every living person. Ou r most ordinary and conventional attitudes seem suddenly twisted into g argoyles and grotesques. Familiar institutions and associations seem at times menacing and malignant. These multiple transformations, which ar e the normal consequence of introducing new media into any society what ever, need special study. The trauma and tension in the daily lives of citizens as described here by McLuhan was only intensified by the arriv al of digital media and the Web in the following decades. The rapidly e volving digital realm held a powerful promise for creative and construc tive good--a promise so alluring that much of the inquiry into this new environment focused on its potential rather than its profound impact o n every sphere of civic, commercial, and private life. The totalizing s cope of the combined effects of computerization and the worldwide netwo rk are the subject of the essays in The Digital Nexus, a volume that re sponds to McLuhan's request for a "special study" of the tsunami-like t ransformation of the communication landscape. These critical excursions provide analysis of and insight into the way new media technologies ch ange the workings of social engagement for personal expression, social interaction, and political engagement. The contributors investigate the terms and conditions under which our digital society is unfolding and provide compelling arguments for the need to develop an accurate grasp of the architecture of the Web and the challenges that ubiquitous conne ctivity undoubtedly delivers to both public and private life."--
Includes bibliographical references.
Issued also in electronic format.
Keywords: digital media -- Social aspects; Digital media -- Political aspects; World Wide Web -- Social aspects; World Wide Web -- Political aspects